Population Pharmacokinetics of Pegcetacoplan in Patients with Geographic Atrophy or Neovascular Age-related Macular Degeneration - Ryan L. Crass, PharmD; Komal Prem, MD; Francois Gauderault, PhD; Ramiro Ribeiro, MD, PhD; Caroline R. Baumal, MD; Brandon Smith, PhD; Daniel Epling, PhD; Sunny Chapel, PhD (Ophthalmology Science)
Objective: To develop a population pharmacokinetic (PK) model to characterize serum pegcetacoplan concentration-time data after intravitreal administration in patients with geographic atrophy (GA) or neovascular age-related macular degeneration (nAMD). Design: Pharmacokinetic modeling. Participants: Two hundred sixty-one patients with GA or nAMD enrolled in 4 clinical studies of pegcetacoplan. Methods: Serum concentration data were pooled from 4 clinical studies. Pegcetacoplan dosing included single intravitreal injections of 4, 10, and 20 mg and multiple intravitreal injections of 15 mg monthly or every other month. Considering a high proportion of samples were below the limit of quantification (BLQ) in serum following intravitreal administration, the M3 method of likelihood-based handling of data BLQ was employed in NONMEM (version 7.4). Covariate model development was performed using stepwise forward (α = 0.05) and backward (α = 0.001) selection. Predicted PK parameters and exposure metrics were generated via simulation in serum and vitreous humor. Main Outcome Measures: Pharmacokinetic parameters. Results: Intravitreal pegcetacoplan displayed absorption-limited (i.e., “flip-flop”) kinetics with median empirical Bayes estimated pegcetacoplan absorption and elimination half-lives of 13.1 days and 4.51 days, respectively. Vitreous exposure was predicted to be >1300-fold higher than serum exposure, with maximum concentrations in serum below the threshold required to elicit systemic pharmacodynamic effects. Drug accumulation from first dose to steady state was predicted to be minimal in serum (mean accumulation ratio = 1.50 with monthly dosing, 1.10 with every-other-month dosing) and vitreous humor (mean accumulation ratio = 1.30 with monthly dosing, 1.10 with every-other-month dosing). Age, sex, and baseline C3 level were identified as significant (P < 0.001) predictors of apparent serum pegcetacoplan clearance after intravitreal administration; however, none of the covariate effects appeared to be clinically meaningful given the low absolute maximum serum concentrations achieved (<5 μg/mL). Concomitant anti-VEGF treatment did not significantly influence vitreous disposition of pegcetacoplan as assessed in a dedicated post hoc covariate model. Conclusions: This population PK model adequately described the serum concentration-time profile of pegcetacoplan after intravitreal administration in adults with GA or nAMD. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.